“Si on ne me fournit pas mes engins, après je peux plus rien faire moi” : les apports de l’analyse de l’activité à la compréhension des processus d’engagement et de désengagement au travail - Amélie Sandoval (Association Recherche et Pratique sur les Activités, 2021)
This article revisits the question of commitment and disengagement at work, by studying their links with the work activity as it is carried out on daily basis by professionals. We mobilize different theoretical perspectives, rooted in psychopathology and in clinical approaches to workplaces and work activity. These perspectives are discussed in relation to data from an intervention carried out in a public cleaning department. This intervention was conducted using the Clinic of Activity approach. Taking one example, we identified a specific configuration of commitment and disengagement at work, its links with the activity, and its subjective implications and effects on daily work.